THE IMPACT OF PHYSICAL ACTIVITY ON METABOLIC SYNDROME AND CARDIOVASCULAR RISK - Mikołaj Asztabski,; Laura Magdalena Sikorska,; Paulina Pudło,; Anna Koman,; Monika Czekalska,; Weronika Worosz,; Martyna Bukowiec,; Luiza Łabuzińska,; Angela Ćwil,; Natalia Morawiecka,; Kacper Byczek, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Metabolic syndrome (MetS) is one of the most serious public-health challenges, affecting approximately 25 % of the adult population worldwide and more than doubling the risk of cardiovascular disease (CVD). It is characterised by the coexistence of abdominal obesity, insulin resistance, dyslipidemia and arterial hypertension, which translates into markedly increased mortality risk. Physical activity (PA) has been identified as a key modifiable factor in the prevention and treatment of this cluster of disorders. The aim of this review is to discuss in detail the impact of various forms of PA on the components of MetS and on CVD risk.Methods and Materials: A systematic review of the scientific literature was carried out, analysing randomised trials, meta-analyses and observational studies that assessed the effectiveness of aerobic, resistance and high-intensity interval training.Conclusions: Regular PA exerts a multidirectional influence on all components of MetS, effectively reducing abdominal obesity, insulin resistance, dyslipidemia and hypertension. Aerobic training shows the greatest efficacy in improving metabolic parameters, whereas the combination of aerobic and resistance modalities provides the most favourable therapeutic outcomes. In secondary prevention of CVD, PA achieves effectiveness comparable to pharmacotherapy and significantly surpasses it in post-stroke patients. The underlying mechanisms include improvements in insulin sensitivity, enhanced glucose uptake by skeletal muscle, and beneficial modulation of adipokine and cytokine profiles. The review underlines the importance of regular PA as a public-health strategy and highlights the need for further research aimed at optimising intervention programs.